The effect of orthodontic appliances on oral microflora: A case‐control study. Issue 1 (27th March 2019) - Dallel, Ines; Merghni, Abderrahmen; Ben Tanfouss, Safa; Tobji, Samir; Ben Amor, Adel; Mastouri, Maha
Abstract: Aim: Several studies have shown that orthodontic treatment affects oral flora. The aim of this study was to evaluate the effect of orthodontic treatment on the oral environment. Materials and Methods: One hundred and one healthy subjects, divided into two groups, were included in this study. The control group consisted of 51 subjects and the test group included 50 patients wearing orthodontic fixed appliances. The microbiological analyses of saliva and bacterial supra‐gingival plaque were performed for the two groups. Results: The results showed that fixed orthodontic appliances alter the oral microbial flora, with a significant predominance of opportunistic Staphylococcus aureus in the oral cavity of patients after orthodontic treatment with fixed appliances. Conclusion: Orthodontic appliances may act as a reservoir for opportunistic pathogens. Hence, our findings underline the necessity of paying more attention to the prevalence of opportunistic bacteria after orthodontic treatment.